ANALYSIS OF THE MEANING OF LOCAL CULTURAL SYMBOLS IN THE 74TH ANNIVERSARY ADVERTISEMENT "TOWARDS A SUPERIOR INDONESIA" GUDANG GARAM CIGARETTES - Arkam, Naufal Dzakwan; Matondang, Muhammad Alfikri (International Journal of Cultural and Social Science, 2025)
This study investigates the semiotic construction of local cultural symbols in Gudang Garam’s 74th-anniversary advertisement, titled “Towards an Excellent Indonesia.” Using Roland Barthes’ semiotic theory, the research explores how visual and auditory elements such as traditional costumes, dances, landscapes, and nationalistic narratives are strategically employed to build a brand image that aligns with nationalism and cultural pride. The analysis reveals that at the denotative level, the advertisement portrays Indonesia’s cultural richness through aesthetic visuals. At the connotative level, however, it embeds ideological narratives that associate the Gudang Garam brand with national unity and excellence. Through the concept of myth, the advertisement constructs a symbolic link between cigarette consumption and national identity a connection that is manufactured rather than organic. Audience interpretations vary: some fully accept the nationalistic message (dominant reading), while others negotiate or reject it due to concerns about the ethical implications of using cultural symbols to promote tobacco products. The study concludes that while the advertisement successfully elicits national pride, it simultaneously raises critical ethical issues regarding cultural commodification in commercial advertising. The findings highlight the complex interplay between visual communication, ideology, and cultural identity, emphasizing the need for a more ethical and culturally respectful approach in future advertising strategies.